Holland’s Holandas: Fabricating Loyalty to the Empire in Quevedo’s El chitón de las tarabillas - Vélez-Sainz, Julio (My University, 2015)
The ailing Spanish empire took August 7 1628 one of its most discussed measures: currency deflation of the copperplate vellón. The Count-Duke of Olivares hired Francisco de Quevedo, who, as a skilful propagandist, wrote his famous prose-work El chitón de las Tarabillas against critics of the deflation. Among other problems associated with the currency, the Dutch were pouring fake vellón into the streets, which caused, according to Quevedo, the devaluation of the silver real. At the same time, the last historical reference present in the piece mentions Spain’s loss of the sites of the Hanseatic Wesel (now in Germany) in August 19, and ‘ s-Hertogenbosch (Bois-le-duc) on September 14, 1629. Moreover, the conflict was at least partially subsidized by the noblemen who enjoyed wearing textiles from the Netherlands. Quevedo intertwines the monetary and the martial conflicts and scatters mentions to several kinds of weaving from Cambray to «gazas» or «Holandas», in which the quality and texture of the garment become a semiotic sign of their owner. Quevedo fabricated a powerful message against those noblemen who criticized the measure while enjoying Dutch spinning. The noblemens’ holandas are scrutinized as to their texture and quality as a metonymy of their loyalty to the Spanish Empire., El imperio español se vio forzado a tomar el 7 de agosto de 1628 una de sus medidas más controvertidas, la devaluación del vellón de cobre. El Conde Duque de Olivares «contrató» a Francisco de Quevedo, para contrarrestar en El chitón de las tarabillas las críticas que la devaluación trajo consigo. Aparte de otros problemas, el vellón se vio afectado por el falso vellón traído por los holandeses que, para Quevedo, había causado la devaluación tanto de este como del real de plata. Para colmo, la guerra no iba bien. La última referencia histórica presente en el texto menciona la pérdida de Wesel el 19 de agosto y ‘ s-Hertogenbosch (Bois-le-duc) el 14 de septiembre de 1629. Los holandeses estaban siendo parcialmente ayudados económicamente por la venta de holandas y otras prendas que vestían los elegantes de la época. Quevedo entremezcla el conflicto monetario y el bélico y disemina menciones a distintos tipos de prendas desde Cambray a «gazas» o «Holandas», en las que la calidad y textura de las mismas se convierten en un signo semiótico del que las lleva. Quevedo fabricó un mensaje poderoso en contra de aquellos que criticaban las duras medidas tomadas mientras se vestían de «holandas» de modo que estas se convertían en una metonimia de su lealtad al Imperio.
Keywords: Francisco de Quevedo, vellón, holanda, El chitón de las tarabillas; Francisco de Quevedo, vellón, holanda, El chitón de las tarabillas